Inequity of Education Financial Resources: A case study of First Nations school funding compared to provincial school funding in Saskatchewan - Carr-Stewart, Sheila; Marshall, Jim; Steeves, Larry (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2011)
In a review of First Nations band-managed school policies, the Department of Indian and Northern Affairs Canada (2002) noted what had been devolved was “the specific operation of the school. What was not devolved was an [education] system which would support the school” (p. 5) delivery of quality educational programming for First Nations’ students. The purpose of this paper is to compare available second level services and funding levels provided in schools operated by a Tribal Council and a provincial school division. Differences in service levels and funding, the authors argue, must be addressed if equitable services and enhanced learning experiences are to be available to all students regardless of school type attended.